Desktop oligosynthesizers: a case study for supporting biotechnology innovation through biosecurity governance, biosafety risk assessment and mitigation strategies - Ami Patel; Elaine Jarvis; Colin Price; Kenny Yeh (Cyberbiosecurity, 2026)
Emerging synthetic biology tools have tremendous potential to revolutionize biotechnology advancement. At the helm of this wave are desktop oligosynthesizers, which are instruments that can quickly generate nucleic acids on-demand potentially without strict third-party oversight. In the biodefense context, this capability can further catalyze innovation in biothreat preparedness and disease surveillance, especially if these platforms become widely adapted. As a result, new biosecurity challenges will arise requiring unique implementation considerations beyond current U.S. policies. Here we present a case study that highlights the use of a desktop oligosynthesizer for a biodefense R&D application. We established new biosafety approvals, biosecurity standards, and quality review processes for Sequence of Concern (SoC) screening to support this effort. Their creation was necessary for translating office-to-lab bench policy based on the 2024 OSTP Framework for Nucleic Acid Synthesis Screening, which the 2025 Executive Order: Improving the Safety and Security of Biological Research may revise in the future. Our experience highlights the importance of multi-stakeholder collaborations to implement effective internal requirements, safeguard critical information, and support biodefense innovation.
Keywords: Biosecurity; Cybersecurity; Defense and Security Studies; Life Sciences